1993
DOI: 10.1007/bf00014931
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of wheat triticin cDNA revealing a unique lysine-rich repetitive domain

Abstract: Polyclonal antibodies were raised against a purified 22 kDa triticin polypeptide (delta) and were used to screen a wheat seed cDNA library in the Escherichia coli expression vector lambda gt11. The isolated cDNA clones were grouped into three families based on their cross-hybridization reactions in DNA dot-blot studies. Southern blots of genomic DNAs extracted from ditelocentric and nullisomic-tetrasomic lines of Chinese Spring wheat, probes with the excised cDNA inserts, indicated that one of the three famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…We report here the linkage relationships among genes encoding low-M glutenin and gliadin proteins in diploid, tetraploid and hexaploid wheats, using DNA hybridization. DNA markers for other storage proteins, such as high-M glutenins (Anderson et al 1989) and triticin (Singh et al 1993) were also included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…We report here the linkage relationships among genes encoding low-M glutenin and gliadin proteins in diploid, tetraploid and hexaploid wheats, using DNA hybridization. DNA markers for other storage proteins, such as high-M glutenins (Anderson et al 1989) and triticin (Singh et al 1993) were also included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Triticin is a minor seed storage protein which accounts for only about 5 % of the total endosperm protein in wheat. It is leguminlike protein and has a lysine-rich repetitive domain in its hyper variable region which offers new opportunities to genetic engineers for increasing lysine content of wheat [36]. Our study found two alleles of triticin showing significant positive effect on bread-making quality parameters.…”
Section: Discussionmentioning
confidence: 59%
“…[3,25,28,29,31,32,36]. Triticin genes are located on the short arm of wheat chromosomes 1A and 1D, near the centromere far away from the major Gli-1/Glu-3 loci [28,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat triticin polypeptides are synthesized specifically during seed development 8 to 21 days after anthesis, and are deposited in the endosperm protein bodies. It may play an important role in determining the functionality of wheat flour dough by participating in thioldisulphide inter-change reactions (Singh et al 1993). Our results from 2-DE also indicated that this protein accumulated at the early stages and reduced gradually at the later stages (Fig.…”
Section: Discussionmentioning
confidence: 99%